Defects and Calcium Diffusion in Wollastonite - Nimasha, S.; Sashikesh, G.; Kuganathan, N.; Davazoglou, K.; Chroneos, A. (MDPI, 2020)
Wollastonite (CaSiO3) is an important mineral that is widely used in ceramics and polymer industries. Defect energetics, diffusion of Ca ions and a solution of dopants are studied using atomistic-scale simulation based on the classical pair potentials. The energetically favourable defect process is calculated to be the Ca-Si anti-site defect cluster in which both Ca and Si swap their atomic positions simultaneously. It is calculated that the Ca ion migrates in the ab plane with an activation energy of 1.59 eV, inferring its slow diffusion. Favourable isovalent dopants on the Ca and Si sites are Sr2+ and Ge4+, respectively. Subvalent doping by Al on the Si site is a favourable process to incorporate additional Ca in the form of interstitials in CaSiO3. This engineering strategy would increase the capacity of this material.
Keywords: Wollastonite; Defects; Diffusion; Atomistic simulation; Mineral